2015
DOI: 10.1093/ehjci/jev057
|View full text |Cite
|
Sign up to set email alerts
|

Normal left-atrial structure and function despite concentric left-ventricular remodelling in a cohort of patients with Anderson–Fabry disease

Abstract: Left-atrial structure and function were relatively normal in our cohort of patients with AFD, who were also judiciously treated with a contemporary strategy that includes renin-angiotensin system antagonism, statins, and ERT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Using CMR with T1 mapping to classify patients with Fabry disease, Bernardini et al reported a progressive impairment of reservoir function, assessed with FT-CMR, according with the reduction of T1 mapping (index of subclinical disease) or the presence of LV hypertrophy (overt heart involvement) (185). Nevertheless, in another study, significant differences in the three LA function components were found only in Fabry disease with significant LV hypertrophy (186).…”
Section: Restrictive Cardiomyopathymentioning
confidence: 99%
“…Using CMR with T1 mapping to classify patients with Fabry disease, Bernardini et al reported a progressive impairment of reservoir function, assessed with FT-CMR, according with the reduction of T1 mapping (index of subclinical disease) or the presence of LV hypertrophy (overt heart involvement) (185). Nevertheless, in another study, significant differences in the three LA function components were found only in Fabry disease with significant LV hypertrophy (186).…”
Section: Restrictive Cardiomyopathymentioning
confidence: 99%
“…Due to inherent risks and limitations of endomyocardial biopsy[ 3 ], non-invasive measures are sought as surrogates for sphingolipid deposition[ 4 , 5 ]. While the focus has been primarily on global changes in cardiac structure and function, such as increasing ventricular mass[ 6 ], atrioventricular uncoupling[ 7 ], and reduced myocardial function[ 8 10 ], recent studies using cardiac magnetic resonance T 1 -mapping techniques show promise in providing improved diagnostic differentiation between other causes of ventricular hypertrophy, as well as the prospect of an earlier marker of disease involvement[ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study AFD patients did not exhibit significant differences in LA size, in contrast with a previous work showing a substantial LA dilation even in AFD without LV hypertrophy [ 30 ]. However, the evidence of LA dilation in AFD remains controversial, as in a cardiac MRI study LA volumes of the AFD group were similar to those seen in the healthy control group [ 32 ]. In our AFD patients, PALS, but not PACS, was substantially lower than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%